Matching the Catalyst Co(Ii)/(I) Formal Potential of a Macrocyclic Complex to the Reversible Potential of Hydrazine Oxidation for the Highest Activity - Zagal-Moya, J; Zagal-Moya, J; Recio-Cortes, F; Recio-Cortes, F (2013)
Sin Editorial Disponible